Social inequalities in health‐related use of time in Australian adolescents - Katia E. Ferrar; Tim S. Olds; Carol A. Maher; Sjaan R. Gomersall (Elsevier, 2012)
Abstract Objective: Young people's socioeconomic position and time use behaviours - including physical activity, sedentary behaviours, social engagement, sleep and cognitive activities - have been associated with health outcomes. This study aimed to describe how time use varies with household income in a representative sample of 9-16 year old Australians. Methods: A random sample of 2,071 9-16 year old Australian children provided household income data and four days' use‐of‐time data. Average daily minutes spent in various types of activities were calculated. Kruskal‐Wallis and Mann Whitney U tests were used to compare time use across the income bands. Results: Higher income participants spent significantly more time playing sport (p<0.0001), including team sports (p=0.0005), and in cognitively demanding behaviours such as school routine (p<0.0001), doing homework (p<0.0001) and playing music (p=0.001) than their low‐income counterparts. Conversely, low‐income participants spent significantly more time watching television (p<0.001) and playing videogames (p<0.0002). There were no differences in sleep or social interaction. Screen time and school‐related activities were the major locations of differences. Conclusions: Time use differences in the areas of sport, school‐related and screen activities may be associated with various health and wellbeing outcomes, and thus be a source of health inequalities. Implications : Socioeconomic‐related time use behaviour differences could be used to develop specific interventions to address health inequalities via interventions addressing time use or income inequalities.